The spatial impact of digital economy on carbon emissions reduction: evidence from 215 cities in China - Zhang, Hao; Qi, Rui; Liu, Yingyue; Wang, Tiantian; Zhong, Feng; Zhou, Qian; Wang, Keying (Frontiers in Environmental Science, 2024)
Within the global framework of carbon emissions constraints, the digital economy has become a new strategy for cities to achieve sustainable development. To estimate the spatial impact of digital economy on carbon emissions, this paper conducts spatial analysis with the spatial Dubin model and panel data of 215 cities in China from 2011 to 2019. The results show that there is a growing regional agglomeration of the digital economy, whereas the spatial evolution of carbon emissions display low liquidity and high stability. Second, the digital economy directly reduces urban carbon emissions, and this conclusion is supported through a series of robustness tests. However, there exist negative spatial spillover effects of digital economy on carbon emissions reduction in neighboring cities. Third, mechanism analysis reveals that the digital economy mainly affects urban carbon emissions through two paths: industrial structure upgrading and green technology innovation. Moreover, the influence of digital economy exhibits heterogeneity, with a more pronounced effect observed in the eastern cities and in large and medium-sized cities, as well as in cities with a high agglomeration of the new energy industry. Our paper not only presents new documentary evidence for understanding the relationship between digitalization and decarbonization, but also provides specific references for policy making to accelerate low-carbon urban development.